Non‐Destructive Surface Energy Measurements on (1 0 0) Galfenol. Issue 1 (16th November 2018) - Van Order, Michael; Sinha, Shayandev; Wang, Hui; Wu, Ruqian; Gaskell, Karen; Flatau, Alison
Abstract: Developing protocols for making thin sheet FeGa (Galfenol) with abnormally grown Goss or Cube grains, which provide maximum magnetostriction, is challenging because the mechanisms that regulate grain boundary mobility and texture development in these alloys are not yet understood. Grain boundary energy models do not account for forces caused by the control of surface energy from atmospheric annealing conditions. By characterizing the surface energy of specific Galfenol grains, we can develop a more accurate thermodynamic framework for modeling abnormal grain growth and texture development. To non‐destructively measure surface energy of specific crystal orientations and overcome passivation layer difficulties in previous studies, a two‐liquid‐phase contact angle method is utilized. A single‐crystal (1 0 0) Fe82 Ga18 is used as a proof of concept for its isotropic surface crystal orientation. The resultant contact angle data shows a high dependence on the use of Ar‐plasma surface preparation to remove native oxides exposing a true interaction between a sessile drop and the Galfenol surface. Experimentally measured surface energy values are in agreement with density functional theory simulations. Surface texture and composition are confirmed using EBSD and XPS measurements. This non‐destructive technique paves the way towards studying surface energies of bare metal surfaces. Abstract : Galfenol is one of the most important alloys that has been widely used as a magnetostrictive material . Here, the surface energy of Galfenol is quantified through a non‐destructive contact angle measurement using two fluids. Density functional theory (DFT) simulations are performed to understand the correlation between surface energy and surface composition.